1987
DOI: 10.1002/1097-0142(19870215)59:4<748::aid-cncr2820590414>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor activity in leukemia cells. Special reference to disseminated intravascular coagulation

Abstract: Tissue factor activity (TFA) of 10(8) leukemia cells was measured in 82 patients with acute nonlymphoid leukemia by the clotting method. The TFA bore a significant correlation to the development of disseminated intravascular coagulation (DIC) in these cases. Mean TFA value with standard deviation (SD) was 8.3 +/- 6.3 U in 48 cases with DIC, which was significantly higher than 0.3 +/- 4.2 U in 34 cases without DIC. Whereas Mean TFA in non-M3 was 0.9 +/- 6.3 U which was significantly lower than 37.2 +/- 2.3 U in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 19 publications
3
39
0
1
Order By: Relevance
“…As TF is expressed broadly in different types of tumors, including solid tumors (5,30,32,37,38) and leukemia (39), hlFVII-LDP-AE has a broad therapeutic potential for lung and other cancers (39)(40)(41). Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…As TF is expressed broadly in different types of tumors, including solid tumors (5,30,32,37,38) and leukemia (39), hlFVII-LDP-AE has a broad therapeutic potential for lung and other cancers (39)(40)(41). Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Wehave previously shown that the severity of DIC in patients with acute myelogenous leukemia is significantly related to the TF activity of their leukemic cells, but not to the leukemic cell counts in peripheral blood and bone marrow (7,9). Amongthe three groups in the present study, no significant difference was observed in the leukemic cell counts at all.…”
Section: Discussionmentioning
confidence: 99%
“…1 mLof factor IX-deflcient plasma were incubated for 3 min at 37°C, after which 0.1 mL of 25 mmol/L CaCl2 solution was immediately blown into the mixture to determine the clotting time. The activity which gave 14 sec of clotting time was arbitrarily defined as 100 U/108 cells (8,9,20), and that which gave clotting time longer than 240 sec was defined as absent. The procoagulant activity of the same samples was also assayed using factor X-deficient plasma using the same procedure.…”
Section: Preparation Of Test Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Acute promyelocytic leukaemia (APL) is the most common myeloid leukaemia associated with thrombotic complications, ultimately leading to DIC. 5 APL is a subtype of acute myelogenous leukaemia with the characteristic chromosome translocation that disrupts the retinoic acid receptor (RAR)-␣ gene on chromosome 17 and fuses it to the promyelocytic leukaemia (PML) gene at chromosome 15, thus resulting in the PML/RAR␣ fusion protein. Beyond pathological expression, TF is also expressed on the surface of bone marrow derived myeloid progenitor cells.…”
Section: Introductionmentioning
confidence: 99%